2021
DOI: 10.1111/febs.16188
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between protein kinase A and the HOG pathway under impaired biosynthesis of complex sphingolipids in budding yeast

Abstract: Complex sphingolipids are important components of the lipid bilayer of budding yeast Saccharomyces cerevisiae, and a defect of the biosynthesis causes widespread cellular dysfunction. In this study, we found that mutations causing upregulation of the cAMP/protein kinase A (PKA) pathway cause hypersensitivity to the defect of complex sphingolipid biosynthesis caused by repression of AUR1 encoding inositol phosphorylceramide synthase, whereas loss of PKA confers resistance to the defect. Loss of PDE2 encoding cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Msn2/4 are activated by Hog1 and involved in the rescue effect of the HOG pathway under complex sphingolipid biosynthesis–defective conditions ( Yamaguchi et al. , 2018 ; Urita et al. , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Msn2/4 are activated by Hog1 and involved in the rescue effect of the HOG pathway under complex sphingolipid biosynthesis–defective conditions ( Yamaguchi et al. , 2018 ; Urita et al. , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 6, these data are consistent with PKA/cAMP signalling pathway that played a hub regulatory role in hyphal development, cell wall synthesis and pellet morphology by cross‐talk with the HOG‐MAPK pathway (Gutin et al ., 2015; de Assis et al ., 2018; Urita et al ., 2021) and CWI pathway (Donlin et al ., 2014; García et al ., 2017) in other fungi.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ura2, which is downregulated in PPK-expressing cells, is phosphorylated by PKA in vitro ( 53 ). Moreover, PKA regulates the activity of Msn2/Msn4 and Yak1 through direct phosphorylation ( 35 , 40 ), and recently, it was suggested that PKA might modulate the activation of the Hog1 pathway during impaired sphingolipid biosynthesis ( 54 ). Previous work has shown that the deletion of YAK1 or MSN2 and MSN4 under conditions of low PKA activity rescues related slow-growth phenotypes ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%